Evaluation and characterization of sunflower (Helianthus annuus L.) germplasm lines: Evaluation and characterization of sunflower (Helianthus annuus L.) germplasm lines - E UMARANI,; A SARITHA,; A V RAMANJANEYULU, (Journal of Oilseeds Research, 2020)
Evaluation and characterization of sunflower germplasm lines is important due to increasing needs of varietalimprovement and it is essential for the gene bank management to avoid duplications. In the present investigation, 67 germplasm lines including B, R lines and inbreds were evaluated and characterized by using six yield and yield contributing traits. Frequency distribution under each group was calculated. Five parameters viz., days to 50% flowering (early-50.56 % and medium-49.44%), days to maturity (early-46.07% and medium-53.93%), head diameter (small-59.55% and medium-40.45%), 100-seed weight (low-11.24% and medium-88.76%) and single plant yield (low1.12% and medium-98.88%) were dimorphic. Whereas, plant height showed five states of expression namely very short (19.10%), short (55.06%), medium (19.10%), tall (4.49%) and very tall (2.25%). Two genotypes namely, CMS104B and HA-291B were found promising for head diameter and HA-2023B for seed yield/plant. Further, based on the objective the genotypes from the different groups will be used in breedingprogramme.